1998
DOI: 10.1002/(sici)1521-4079(1998)33:5<681::aid-crat681>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Misfit Strain Relaxation by Dislocations in InAs Islands and Layers Epitaxially Grown on (001)GaAs Substrates by MOVPE

Abstract: qF gner niversity veipzigD pulty of ghemistry nd winerlogyD snstitute of winerlogyD grystllogrphy nd wterils ieneD vinn estrsse QÀS @eAD HRIHQ veipzigD pFFqF grystF esF ehnolF QQ IWWV S TVI± ±UHS RT B

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…The system provides sufficient energy to nucleate partial half dislocation loops, assisted by the removal of surface steps 20,27 and high temperature ͑the nucleation rate is largely affected by the temperature͒. ͑2͒ Most of the loops are repelled by the dislocation line tension, but some loops can overcome the energy barrier either by being pinned during island growth or by fluctuations in local stresses during the growth.…”
Section: ͑1͒mentioning
confidence: 99%
See 1 more Smart Citation
“…The system provides sufficient energy to nucleate partial half dislocation loops, assisted by the removal of surface steps 20,27 and high temperature ͑the nucleation rate is largely affected by the temperature͒. ͑2͒ Most of the loops are repelled by the dislocation line tension, but some loops can overcome the energy barrier either by being pinned during island growth or by fluctuations in local stresses during the growth.…”
Section: ͑1͒mentioning
confidence: 99%
“…9,20 Chen et al 11 also suggested a mechanism of a 90°partial dislocation being generated from the island surface to remove a pre-existing stack fault and consequently forming a 90°perfect sessile dislocation. However, there appears to be no previously reported evidence for the 30°partial misfit dislocations to be generated at the surface of quantum dots.…”
mentioning
confidence: 99%
“…For small devices, defects such as dislocations and lattice mismatch in hetero epitaxial structures affect significantly to the overall performance of device. Especially a major defect, dislocations play a major role in the growth and properties of epitaxial layers (Wagner, 1998). Thus it is important to quantify dislocation distribution and evaluate dislocation density in epitaxial layers.…”
Section: Introductionmentioning
confidence: 99%
“…The strain relaxation phenomena occurring at early stages of growth in these uncoalesced InAs islands strongly affect the microstructure of the coalesced thin films. The misfit dislocation (MD) microstructure in InAs islands and films grown by MOVPE, as studied by HRTEM [18], includes 901 pure edge as well as 601 mixed dislocations at heterointerface in the InAs. The high density of threading dislocations often associated with InAs films deposited directly on GaAs (1 0 0) can degrade the device performance.…”
Section: Introductionmentioning
confidence: 99%